Perlindungan Hukum Bagi Konsumen Korban Penipuan Tiket Konser Di Era Digital - Kusumawardana, Amanda Salsabila (Peneliti.net, 2025)
This study discusses the legal regulations that apply to protect consumers who are victims of concert ticket fraud in the digital era, and identifies the responsibilities that must be fulfilled by business actors. From the results of the study, it was found that technological advances, especially in the music sector, have made it easier for consumers to access but have also provided space for cybercrime, such as ticket fraud. The Coldplay concert ticket fraud case in Indonesia highlights the importance of legal protection even though there are regulations that still face obstacles in their implementation. Therefore, strengthening legal protection is very necessary to ensure security in transactions. There is a Consumer Protection Law (UUPK) and several articles in the Electronic Information and Transactions Law (UU ITE) which are expected to protect consumer rights. However, this legal protection must be supported by consumer awareness and the actions of actors to create a safe transaction ecosystem. The responsibilities of business actors include providing accurate information, ensuring product quality, and maintaining transaction security. Business actors are required to fulfill consumer rights, including providing compensation in the event of a loss.